(untitled) (CAHIERS MAGELLANES-NS, 2024)
: The article presents ideas about the technology of directing students to professional activity and the structure of professional activity. The content of the concepts that are common for the creation of conception to the formation of students’ professional competence was determined, the structure of this competence, the stages and conditions necessary for its formation were considered.